Pengaruh Informasi Asimetri, Partisipasi Anggaran dan Komitmen Organisasi Terhadap Kesenjangan Anggaran pada PT. Puri Suma Mandiri - Herlambang Pudjo Santosa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Increase or decrease The budget gap depends on the extent to which the individual is more self-absorbed or works for the benefit of his organization. This is an actualization of the level of commitment he has. Commitment shows strong confidence and support for the values and goals (goals) to be achieved by the organization. For highly committed individuals, the achievement of organizational goals is an important thing that must be achieved, as well as having a positive outlook and doing the best for the benefit of the organization. Based on the background of the problems mentioned above, there was an interest in conducting research with the title: The Effect of Information asymmetry, Budget Participation and Organizational Commitment to Budget Gaps in PT. Puri Suma Mandiri. The population in this study were Heads of Departments and Section Heads who took part and played an important role in decision making in the PT office. Puri Suma Mandiri Surabaya, which has 35 people. While the analysis technique used is multiple linear regression. After knowing the problem, researching and discussing the results of research on the influence of asymmetric information, budget participation, and organizational commitment to the budget gap, several conclusions can be drawn as follows: Asymmetric information variables, budget participation, and organizational commitment have a simultaneous effect on budget gaps. Partial variables of information asymmetry, budget participation, and organizational commitment have a partial influence on budget gaps.